Ultra-Low Power, Process-Tolerant 10T (PT10T) SRAM with Improved Read/Write Ability for Internet of Things (IoT) Applications - Pooran Singh; Santosh Kumar Vishvakarma (Journal of Low Power Electronics and Applications, 2017)
In this paper, an ultra-low power (ULP) 10T static random access memory (SRAM) is presented for Internet of Things (IoT) applications, which operates at sub-threshold voltage. The proposed SRAM has the tendency to operate at low supply voltages with high static and dynamic noise margins. The IoT application requires battery-enabled low leakage memory architecture in a subthreshold regime. Therefore, to improve leakage power consumption and provide better cell stability, a power-gated robust 10T SRAM is presented in this paper. The proposed cell uses a power-gated p-MOS transistor to reduce the leakage power or static power in standby mode. Moreover, due to the stacking of n-MOS transistors in 10T SRAM latch and by separating the read path from the 10T SRAM latch, the static and dynamic noise margins in read and write operations has shown significant tolerance w.r.t. the variations in device process, voltage, and temperature (PVT) values. The proposed SRAM shows significantly improved performance in terms of leakage power, read static noise margin (RSNM), write static noise margin (WSNM), write ability or write trip point (WTP), read–write energy, and dynamic read margin (DRM). Furthermore, these parameters of the proposed cell are observed at 8-Kilo bit (Kb) SRAM and compared with existing SRAM architectures. From the Monte Carlo simulation results, it is observed that the leakage power of a proposed low threshold voltage-LVT 10T SRAM is reduced by 98.76%, 98.6%, 6.7%, and 98.2% as compared to the LVT C6T, RD8T, LP9T, and ST10T SRAM, respectively, at 0.3V VDD. Additionally, in the proposed 10T SRAM, parameters such as RSNM, WSNM, WTP, and DRM are improved by 3×, 2×, 1.11×, and 1.32×, respectively, as compared to C6T SRAM. Similarly, the proposed 10T SRAM shows an improvement of 1.48×, 1.25×, and 1.1× in RSNM, WSNM, and WTP, respectively, in the parameters as compared to RD8T SRAM at 0.3 V VDD.